Pengaruh Pengawasan dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Permodalan Siak Kabupaten Siak Sri Indrapura (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of supervision and work motivation on employee performance at PT. Siak Capital Siak Regency Sri Indrapura. This type of research is a quantitative research using the multiple linear regression method. The population in this study is all employees of PT. Siak Capital with a sampling technique using a saturated sampling technique or known as the census technique which totals 60 respondents. Data collection was carried out by distributing questionnaires to respondents. The research data was analyzed using the SPSS program. The results of this study show that partial supervision and work motivation have a significant effect on employee performance at PT. Siak Capital Siak Regency Sri Indrapura. The results of the test in silhouette showed that supervision and work motivation had a significant effect on employee performance at PT. Siak Capital Siak Regency Sri Indrapura. The R Square value is 0.801 or 80.1%, indicating that the supervision and work motivation variables have a significant effect on employee performance, namely 80.1% and the remaining 19.9% ​​is influenced by other variables not included in this research.